Do You Know What I Mean? Brain Oscillations and the Understanding of Communicative Intentions - Brunetti, Marcella; Zappasodi, Filippo; Marzetti, Laura; Perrucci, Mauro G.; Cirillo, Simona; Romani, Gian L.; Pizzella, Vittorio; Aureli, Tiziana (Frontiers in Human Neuroscience, 2014)
Pointing gesture allows children to communicate their intentions before the acquisition of language. In particular, two main purposes seem to underlie the gesture: to request a desired object (imperative pointing) or to share attention on that object (declarative pointing). Since the imperative pointing has an instrumental goal and the declarative an interpersonal one, only the latter gesture is thought to signal the infant’s awareness of the communicative partner as a mental agent. The present study examined the neural responses of adult subjects with the aim to test the hypothesis that declarative rather than imperative pointing reflects mentalizing skills. Fourteen subjects were measured in a MEG environment including 4 conditions, based on the goal of the pointing–imperative or declarative–and the role of the subject–sender or receiver of pointing. Time-Frequency modulations of brain activity in each condition (Declarative Production and Comprehension, Imperative Production and Comprehension) were analyzed. Both low BETA and high BETA power were stronger during Declarative than Imperative condition, in anterior cingulated cortex and right posterior superior temporal sulcus, respectively. Furthermore, high GAMMA activity was higher in right temporo-parietal junction during the sender than receiving condition. This suggests that communicative pointing modulated brain regions previously described in neuroimaging research as linked to social cognitive skills and that declarative pointing is more capable of eliciting that activation than imperative. Our results contribute to the understanding of the roles of brain rhythm dynamics in social cognition, thus supporting neural research on that topic during developmental both in typical and atypical conditions, such as autism spectrum disorder. In particular, the identification of relevant regions in a mature brain may stimulate a future work on the developmental changes of neural activation in the same regions.